Liver Dysfunction and Oxidative Stress in Streptozotocin-Induced Diabetic Rats: Protective Role of Artemisia Turanica - Hassan Bgheri Yazdi1,Vida Hojati; Abdolhossein Shiravi; Sara Hosseinian; Gholamhassan Vaezi; Mousa- (Korean Pharmacopuncture Institute, 2019)
Objectives: Oxidative stress plays a central role in diabetes-induced complications. In the present study, the protevtive effect of Artemisia turanica (A. turanica) was evaluated against diabetes-induced liver oxidative stress and dysfunction. Methods: Fifty male Wistar rats were randomly divided into five groups: control, diabetic, diabetic + metformin, diabetic + A. turanica extract, and diabetic + A. turan ica extract + metformin. Experimental diabetes was induced by a single-dose (55 mg/kg, intraperitoneally (ip)) injection of streptozotocin (STZ). Metformin (300 mg/kg) and A. turanica extract (70 mg/kg) were orally administrated three days after STZ injection for four weeks. The levels of malondialdehyde (MDA), total thiol content and superoxide dismutase (SOD) and catalase activities were measured in the liver tissue. Serum glucose concentration, aspartate aminotransferase (AST) and alanine aminotransferase (ALT) activities were also determined. Results: In the diabetic group, serum glucose concentration, serum AST and ALT activities and liver MDA level were significantly higher while tissue total thiol content as well as catalase and SOD activities were lower, compared to the control group. Serum glucose in diabetic rats treated with metformin + A. turanica extract showed a significant decrease compared with the diabetic group. In all the A. turanica extract and metformin treated groups, serum ALT, tissue MDA level, total thiol content and SOD activity significantly improved compared with the diabetic rats. However, treatment of the diabetic rats only with metformin could not significantly change the activities of catalase and AST compared with the diabetic group. Conclusion: These findings suggested that A. turanica extract had a therapeutic effect on liver dysfuncyion and oxidative stress induced by diabetes, that may be probably due to its antioxidant and antiinflammatory effects.